Economic Internal Rate of Return and Sensitivity Analysis in Water Treatment Plant Project Evaluation - Miranti, Khadijah Ayu; Nugroho, Anggoro Budi (Journal of Business and Management, 2014)
In 2014 the increased clean water service only reach up to 50% of the total population in Indonesia, or about 160.000 l/s. The needs of a lot improvement in this sector make clean water as business commodity. PT. TeknoTirta Nusantara (TTN) and PDAM KabupatenSerang are interested to developing the quality and quantity of clean water supply in KabupatenSerang. This research are to calculate the investment feasibility study, conducting risk analysis through sensitivity analysis method, assessing the performance of the company using economic value added method, last to identify and measure of financial risks that threaten a company or projects (risk mapping).Keywords: clean water, feasibility study, sensitivity analysis, economic value added, risk mapping.